2015
DOI: 10.1093/rheumatology/kev003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of long-term remission in lupus nephritis patients: a retrospective analysis over 30 years

Abstract: Renal histology with WHO class IV predicted a poor long-term remission rate. Age, sex, ethnicity, serological parameters and treatment received did not predict long-term remission. Renal flares can occur up to 15 years after a patient has gone into remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 14 publications
0
14
0
4
Order By: Relevance
“…88 Finally, open-label extensions of RCT and observational studies suggest that the majority of kidney flares tend to occur within the first 5–6 years of therapy; after this point, their rate decreases significantly but does not reach zero. 34 62 78 89 90…”
Section: Resultsmentioning
confidence: 99%
“…88 Finally, open-label extensions of RCT and observational studies suggest that the majority of kidney flares tend to occur within the first 5–6 years of therapy; after this point, their rate decreases significantly but does not reach zero. 34 62 78 89 90…”
Section: Resultsmentioning
confidence: 99%
“…Different studies showed that sustained renal remission is associated with a better prognosis in LN [ 37 ], notably with reduced progression to chronic kidney disease, ESRD and mortality [ 38 ]. A Korean study suggested that, in diffuse PLN, remission of proteinuria is an independent prognostic marker associated with improved renal and patient survival, regardless of the time between the biopsy and the normalization of proteinuria or the recurrence of proteinuria after remission [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that renal biopsies demonstrating diffuse proliferative (class IV) LN and increased glomerular activity indices are associated with a poorer long-term prognosis [ 31 , 32 , 43 , 44 ], an increased likelihood of re-flare [ 45 ], and increased chronicity scores on subsequent renal biopsies with glomerulosclerosis and consequent renal functional deterioration [ 46 ]. Given the invasive nature of renal biopsies, there has been considerable interest in the identification of urinary biomarkers that accurately reflect renal disease activity scores and/or proliferative nephritis.…”
Section: Discussionmentioning
confidence: 99%